Exploring Religious Identity and Well-Being of Generation Z: Mediating Role of Digital Engagement - Murniasih, Farhanah; Cebba, Abdul Hamid; Namira Daffani Sabina (Jurnal Diversita, 2024)
The primary challenges faced by Generation Z include high levels of stress, vulnerable mental health, and social pressures that can impede their overall well-being. In addressing these challenges, it is crucial to explore factors that can contribute to enhancing their well-being. This study aims to investigate the relationship between religious identity and psychological well-being among Generation Z in Indonesia, as well as the mediating role of digital engagement in this relationship. Generation Z encounters various difficulties, including social pressures, anxiety, and uncertainty about the future, all of which can impact their well-being. Religious identity, encompassing religious affiliation and beliefs, is considered a factor that can provide emotional support and enhance well-being. This research employed a survey method involving 753 respondents from Generation Z in Indonesia, who were recruited through an online questionnaire. The findings indicate that religious identity positively influences psychological well-being, both directly and through increased digital engagement. These findings have significant implications for religious organizations and policymakers in leveraging digital platforms to support the psychological well-being of Generation Z. The study also opens avenues for further research on how digital technology can be optimally utilized in the context of religion and mental well-being.